Revealing the immune perturbation of black phosphorus nanomaterials to macrophages by understanding the protein corona - Jianbin Mo (Nature Portfolio, 2018)
The formation of a protein corona around nanomaterials is known to have significant effects upon materials in biological applications. Here, the authors report on a study into understanding the protein corona formed on black phosphorus and the implications for interactions with macrophages.